Chronic Fatigue Syndrome - diagnostic challenge in a general practice - Banaszczyk, Katarzyna; Puk, Oskar; Maliszewska, Adrianna; Owsiany, Michał (Journal of Education, Health and Sport, 2018)
Introduction: Chronic fatigue syndrome is a heterogeneous disease associated with a vary of symptoms but with severe, prolonged fatigue as the core symptom associated with the disease. This is a condition characterized by an unreasonable sense of tiredness lasting over 6 months that cannot be explained by other conditions. In spite of more and more intensive research, the chronic fatigue syndrome is still insufficiently known and often overlooked in diagnostics. Aim: The intention of this article is to obtain and summarize current information about the diagnosis of chronic fatigue syndrome and also to increase the awareness of the problem in general medical practice. Materials and methods: The systematic literature search was performed by the use of Pubmed as a database. An extensive literature study has been carried out covering the period from 2007 until 2018. Results: This report presents a differential diagnosis of CFS and preliminary tests, that we should do to exclude other diseases associated with fatigue. The article describes presently used questionnaires in CFS – COMPASS and The Chalder Fatigue Scale. The issue of the role of infections in the ethiopathogenesis of CFS has also been raised. The attention was paid to EBV, because of the widespread of its carrier state. The article presents also the potential role of hipocortisolism and α-melanocorticotropin hormone as the hormonal markers of CFS. Conclusions: In conclusion, there is an essential need to discover possible markers of CFS and to create standardized diagnostic procedure for this underestimated disease. Analysis of recent studies allow us to create simple scheme which general practicers can use to diagnose CFS and rise quality of life of many patients which is heavily impaired by as common symptom as chronic fatigue is.